Penerapan Sistem Pakar untuk Diagnosis Penyakit pada Tanaman Cabai dengan Menggunakan Teorema Bayes - Titus Ariyanto Hipir; Semlinda J. Bulan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to develop an expert system in diagnosing diseases in chili plants using the Bayes Theorem method. Chili plants are one of the vegetable commodities in Noelbaki Village, Kupang Regency, often experiencing disease attacks that are detrimental to crop yields. Farmers' lack of knowledge about plant diseases and how to deal with them is a serious challenge. The expert system was designed to mimic an expert's ability to diagnose diseases based on the symptoms displayed. The Bayes Theorem method was chosen for its ability to analyze symptom data quickly and accurately. The results of this research are expected to help farmers recognize patterns of disease attack, so as to increase local food production and security, as well as provide practical solutions in disease identification and improve farmers' understanding of the right treatment